Bin there, done that - Cheah, Ann Ying (Nanyang Technological University, 2021)
Every year, the global cosmetics industry is responsible for producing 120 billion units of packaging waste. In Singapore, the beauty and personal care market is one of the fastest-growing consumer markets. The amount of cosmetics packaging consumed in Singapore has been rising from 116.5 million units in 2009 to 142 million units in 2019 - this includes our daily shampoo and soap products which most Singaporeans consume. The increasing consumption of cosmetics packaging means more waste produced. Coupled with low recycling rates and the high carbon footprint from the industry, this is a highly unsustainable and pertinent problem.